Transarterial Chemoembolization for Hepatocellular Carcinoma in Clinical Practice: Temporal Trends and Survival Outcomes of an Iterative Treatment - Pelizzaro, Filippo; Haxhi, Selion; Penzo, Barbara; Vitale, Alessandro; Giannini, Edoardo G.; Sansone, Vito; Rapaccini, Gian Ludovico; Di Marco, Maria; Caturelli, Eugenio; Magalotti, Donatella; Sacco, Rodolfo; Celsa, Ciro; et al. (Frontiers in Oncology, 2022)
Background: Transarterial chemoembolization (TACE) is one of the most frequently applied treatments for hepatocellular carcinoma (HCC) worldwide. In this study, we aimed at evaluating whether and how TACE application and repetition, as well as the related outcome, have changed over the last three decades in Italy. Methods: Data of 7,184 patients with HCC were retrieved from the Italian Liver Cancer (ITA.LI.CA) database. Patients were divided according to the period of diagnosis in six cohorts: P1 (1988-1993), P2 (1994-1998), P3 (1999-2004), P4 (2005-2009), P5 (2010-2014), and P6 (2015-2019). All the analysis were repeated in the overall patient population and in Barcelona Clinic Liver Cancer (BCLC) B patients, who are the subgroup of HCC patients originally supposed to receive TACE according to guidelines. TACE was either defined as the first or the main (more effective) treatment. Results: The proportion of patients receiving TACE as first or main therapy declined over time, and less than 50% of BCLC B patients were treated with chemoembolization from P3 onwards. Conversely, TACE was widely used even outside intermediate stage. Survival of TACE-treated patients progressively increased from P1 to P6. Although TACE was performed only once in the majority of patients, there was an increasing proportion of those receiving 2 or ≥3 treatments sessions over time. The overall survival (OS) of patients undergoing repeated treatments was significantly higher compared to those managed with a single TACE (median OS 40.0 vs. 65.0 vs. 71.8 months in 1, 2 and ≥3 TACE groups, respectively; p<0.0001). However, after a first-line TACE, the adoption of curative therapies provided longer survival than repeating TACE (83.0 vs. 42.0 months; p<0.0001), which in turn was associated with better outcomes compared to systemic therapies or best supportive care (BSC). Conclusions: Despite a decline in the percentage of treated patients over time, TACE has still an important role in the management of HCC patients. The survival of TACE-treated patients gradually improved over time, probably due to a better patients’ selection. Iterative TACE is effective, but an up-ward shift to curative therapies provides better outcomes while transition to systemic therapies and BSC leads to a worse prognosis.